Sustainable intensification for a larger global rice bowl - Yuan, S.; Linquist, B.A.; Wilson, Lloyd T.; Cassman, Kenneth G.; Stuart, A.M.; Pede, Valerien O.; Miro, B.; Saito, Kazuki; Agustiani, N.; Aristya, V.E.; Krisnadi, L.Y.; Zanon, A.J.; et al. (Springer, 2021)
Future rice systems must produce more grain while minimizing the negative environmental impacts. A key question is how to orient agricultural research & development (R&D) programs at national to global scales to maximize the return on investment. Here we assess yield gap and resource-use efficiency (including water, pesticides, nitrogen, labor, energy, and associated global warming potential) across 32 rice cropping systems covering half of global rice harvested area. We show that achieving high yields and high resource-use efficiencies are not conflicting goals. Most cropping systems have room for increasing yield, resource-use efficiency, or both. In aggregate, current total rice production could be increased by 32%, and excess nitrogen almost eliminated, by focusing on a relatively small number of cropping systems with either large yield gaps or poor resource-use efficiencies. This study provides essential strategic insight on yield gap and resource-use efficiency for prioritizing national and global agricultural R&D investments to ensure adequate rice supply while minimizing negative environmental impact in coming decades.